Proceedings of the 2007 ACM/IEEE Conference on Supercomputing 2007
DOI: 10.1145/1362622.1362655
|View full text |Cite
|
Sign up to set email alerts
|

Parallel hierarchical visualization of large time-varying 3D vector fields

Abstract: We present the design of a scalable parallel pathline construction method for visualizing large time-varying 3D vector fields. A 4D (i.e., time and the 3D spatial domain) representation of the vector field is introduced to make a timeaccurate depiction of the flow field. This representation also allows us to obtain pathlines through streamline tracing in the 4D space. Furthermore, a hierarchical representation of the 4D vector field, constructed by clustering the 4D field, makes possible interactive visualizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…The preprocessing of such a method is quite expensive, and Yu et. al [56] have reported that less than one second of rendering required approximately 15 minutes of preprocessing time.…”
Section: Chapter 6 Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preprocessing of such a method is quite expensive, and Yu et. al [56] have reported that less than one second of rendering required approximately 15 minutes of preprocessing time.…”
Section: Chapter 6 Discussion and Conclusionmentioning
confidence: 99%
“…We can drop the term e −iω 0 t by demodulation, and extend our argument to multiple dimensions so that 56) where…”
Section: Frequency and Phase-encodingmentioning
confidence: 95%
“…Therefore, we have implemented both in the event we suspected drift in the placement of the streamlines. Our visualization subsystem is capable of generating the 3D vector field using glyphs or streamlines [10][11][12][13][14]. The glyph based approach draws an arrow at a point in 3D space that is oriented with the vector flow as shown in figure 4.…”
Section: Visualization Detailsmentioning
confidence: 99%
“…Other solutions to the load-balancing issues are presented in [7,14,18]. Rather than adapting the scheduling of particle traces, they statically partition the domain into blocks of approximately equal workload by using different schemes.…”
Section: Parallel Particle Advectionmentioning
confidence: 99%